The Effect Compensation and Work Motivation on Job Satisfaction with Work Environment as Moderating Variable - Christine Natania Zefanya; Avi Permata Sari (Journal of Management and Digital Business, 2024)
Purpose – This study aims to obtain empirical evidence about the influence of compensation and work motivation on job satisfaction with the work environment as a moderating variable. Design/methodology/approach – This research uses a quantitive type of research was conducted using a questionnaire distributes to employees at the company who work in one of the instituions or companies, namely 160 number of questionnaires distributed via social media. Each questionnaires, distributed contains 49 statement for respondents to answer. From the distribution of the questionnaire, 160 respondents to answers from millenial employees in Indonesia. To get the result of this research, research used PLS SEM Version 3.0. Findings – This result of this research found that compensation affects a positive and has a significant effect on job satisfaction, work motivation affects and has a insignifficant effect on job satisfaction, the work environment can weaken the relationship between compensation and job satisfaction and the work environment can strengthen the relationship between. Research limitations/implications – This study has several limitations that must be considered when interpreting the results. First, the sample size is limited to millennial employees in Indonesia, which may not fully represent diversity and therefore may not be relevant for other generations or in different cultural contexts. Implications for future research include the need to expand the sample size to include more by influencing more diverse generations, both in terms of size and geographical spread, as well as extending the research period to obtain more longitudinal data. Researchers can also explore qualitative methods to gain a deeper understanding of millennial employee motivation in Indonesia. In addition, the insignificant effect of the independent variable Work Motivation on Job Satisfaction suggests the need for further investigation into the relationship between the two by considering other factors that may act as mediators or moderators.